2002
DOI: 10.1046/j.1365-2168.2002.02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor but not peritoneal lavage increases survival rate after experimental abdominal contamination and infection

Abstract: In these CMRTs of intra-abdominal contamination and infection, peritoneal lavage was not beneficial, but when lavage was combined with subcutaneous administration of G-CSF mortality was reduced and the local and systemic cytokine response was downgraded. Results from these CMRTs were used directly to define the trial conditions of a randomized clinical trial with G-CSF. Peritoneal lavage is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
(23 reference statements)
0
18
0
Order By: Relevance
“…In a model of endotoxin shock in mice, it was also demonstrated that the P2Y12 receptor antagonist clopidogrel attenuates the drop in blood platelet count and fibrin deposition in lungs, as well as modulating gene expression in peripheral blood cells [5]. To obtain further evidence for a beneficial effect of antiplatelet drugs in sepsis, we studied the effects of clopidogrel on sepsis in mice induced by polymicrobial peritoneal contamination and infection (PCI) [8].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a model of endotoxin shock in mice, it was also demonstrated that the P2Y12 receptor antagonist clopidogrel attenuates the drop in blood platelet count and fibrin deposition in lungs, as well as modulating gene expression in peripheral blood cells [5]. To obtain further evidence for a beneficial effect of antiplatelet drugs in sepsis, we studied the effects of clopidogrel on sepsis in mice induced by polymicrobial peritoneal contamination and infection (PCI) [8].…”
mentioning
confidence: 99%
“…It monitors the viscoelastic properties of a clot induced in whole blood samples in vitro. Clotting time (CT), that is, the lag phase between intrinsic or extrinsic activation of coagulation and start of clot formation, is mainly dependent on plasma coagulation factors and inhibitors, whereas clot formation time (CFT), clot formation rate (CFR) and maximum clot firmness (MCF) predominantly depend on plasma fibrinogen level and blood platelet count [8,9]. As shown in Table 1, 6 h after PCI, we observed a significant prolongation of CT and CFT as well as a decrease in CFR and MCF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…the effectiveness of different combinations of H 1 + H 2 -receptor antagonists in preventing cardio-respiratory instabilities in pigs [21]. Furthermore, this concept was applied to studies in rodents investigating the effect of the immunomodulating growth factor G-CSF (granulocyte-colony stimulating factor) applied as a prophylaxis on the course and outcome of peritonitis and sepsis in rats [19,22,44]. The results of these pre-clinical experiments in rats were used for the development of a clinical study protocol which was published in three parts [45][46][47] before the prospective, randomised, clinical study was successfully conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Laparotomy was performed through a midline incision of two-centimeter length and the inoculum was injected i.p. into the pelvic region of the rats [26]. The wound was closed in two layers using an interrupted absorbable Vicryl ® 3-0 suture technique (Ethicon, Hamburg, Germany).…”
Section: Sepsis Induction and Treatmentmentioning
confidence: 99%